MOVILIDAD ESPACIAL Y HORTICULTURA EN EL VALLE MEDIO DE RÍO NEGRO: LA CONSTRUCCIÓN DE UN TERRITORIO MIGRATORIO - Flavio D. Abarzúa; María S. Brouchoud (Boletín Geográfico)
This paper aims to characterize the Middle Valley of Río Negro like a horticultural land and show the processes of spatial mobility that allow considered as an migratory territory. This will present the description of two producer’s trajectories Bolivian who work in horticultural production in this productive space. The study area has developed in the last decades a considerable expansion of horticultural production, currently concentrating 48% of the province's surface devoted for this type of production. The cultivation of tomato for industry, onion for the domestic market and for export, and the vegetables for fresh consumption aimed at regional markets and local fairs are the main options in this type of production. In this dynamic activity, migrant families, mainly of Bolivian, have been a central component since they are the ones that mostly involved in the cultivation and marketing of horticultural products. In the life experiences of these migrants the "migratory habitus” intersect, is the habit of "leaves" their homes to different places, and the possibility of building their migratory territory. In this sense, migratory, work and productive trajectories of Lourdes and David presented here allows us to approach the analysis of these processes. This work is addressed from an interdisciplinary approach in which the contributions of anthropology and sociology add to geography, and allow closer to understanding the complexity that characterizes migration. Thus, the concepts of territory, migratory territory, spatial mobility and trajectories are very important elements in the organization or this paper. This work is mainly based on a qualitative design, in which the case studies and biographical accounts are established as key pieces of research. In this sense, observations, records and interviews while within the study area, combined with secondary data coming from the systematization of population censuses, agricultural censuses and surveys and specific bibliography.